Synchronizations in Complex Systems Dynamics Through a Multifractal Procedure - Vlad Ghizdovat; Diana Carmen Mirila; Florin Nedeff; Dragos Ioan Rusu; Oana Rusu; Maricel Agop; Decebal Vasincu (Entropy)
The dynamics of complex systems often exhibit multifractal properties, where interactions across different scales influence their evolution. In this study, we apply the Multifractal Theory of Motion within the framework of scale relativity theory to explore synchronization phenomena in complex systems. We demonstrate that the motion of such systems can be described by multifractal Schrödinger-type equations, offering a new perspective on the interplay between deterministic and stochastic behaviors. Our analysis reveals that synchronization in complex systems emerges from the balance of multifractal acceleration, convection, and dissipation, leading to structured yet highly adaptive behavior across scales. The results highlight the potential of multifractal analysis in predicting and controlling synchronized dynamics in real-world applications. Several applications are also discussed.